The Musical Force of the Magnetic Field: On the Latest Creative Phase in the Works of Jasna Veličković. - Ilić, Ivana (Contemporary Music Review)
Since 2008, Jasna Veličković has been experimenting with and researching within the sound world of the magnetic field—the omnipresent, yet usually completely silent elements in human life. Her journey into the unknown started with an exploration of the sound produced by manipulating coils as parts of complex sound systems, including classical instruments as sound sources. A purely serendipitous event in 2013 led her to the discovery that magnets can also produce sounds when applied to coils in certain ways. This discovery ultimately resulted in the invention of the Velicon, the instrument which she has been composing for and performing on ever since. The investigations of the musical force of the magnetic field also led to the introduction of other seemingly silent objects as sound sources. In this article, I aim to investigate these works both from the diachronic and the synchronic perspective. The key questions will include: (1) mapping Jasna Veličković's referential worlds—an intricate encounter between music and science/technology, (artistic) experimentation, and electronic music—viewed from the composer's personal, Serbian, and 'global' perspective; (2) the nature of Veličković's creative process with regard to the reconfiguration of the relationship between composing, experimenting, and improvising; (3) the ramifications of Veličković's way of breaking loose from the conventional composer-performer-listener chain; and (4) analytical remarks on the prospects of musical structure within the magnetic sound.